Insights on Payment for Environmental Services in Fisheries: A Systematic Review - Laura Develey; Leandra Regina Gonçalves (Coasts)
In the context of the prevailing environmental crisis, one innovative approach with the potential to promote inclusive conservation is payment for environmental services (PES). While numerous studies have documented the efficacy of PES in terrestrial ecosystems, mechanisms tailored to marine ecosystems remain relatively unexplored. The objective of this article is to conduct a systematic literature review to identify the essential components of a PES mechanism for fisheries and to map the lessons, challenges, and opportunities associated with it. Three databases were explored: Web of Science, ScienceDirect, and Scopus. Using Boolean operators, we searched for articles containing the following terms in the title, abstract, and/or keywords: “payment for ecosystem services” AND “fish*” and “payment for environmental services” AND “fish*”. Twenty-six articles focusing in depth on PES in the context of fisheries were identified. The results indicate that PES is a tool that can reconcile conservation and social objectives while offering numerous benefits for fisheries management. Nevertheless, it is imperative to meticulously evaluate the circumstances under which PES can meaningfully contribute to the inclusive conservation of marine and coastal ecosystems rather than assuming that it is a universal policy panacea.